Outros de nós que estão mortos - Leal, Bruno Santos Barros (2021)
This dissertation proposes to tell a story from early last century. In the interior of the Cariri cearense, in a place called Caldeirão de Santa Cruz do Deserto, thousands of peasants who were killed in one of the greatest massacres in Brazilian history. This story is based on the work Nossos Mortos (2018) by Teatro Máquina, in which the Caldeirão massacre is intertwined with the myth of Antigone, with the intention of unearthing one of the countless Brazilian stories that still needs to be told. With this contribution, remains the question: how to make those dead ours? Throughout the dissertation an ethic is thought in the face of these forgotten and placeless deads and, with this, the possibility of other writings in history, not for the documents of the official culture, but affiliated to the memory of the defeated and the dead